SURVEI TINGKAT KEBUGARAN JASMANI MASYARAKAT USIA DI ATAS 40 TAHUN PADA ANGGOTA ARCA HASH CLUB KABUPATEN MADIUN - PUTRA, ARDYAN WIDYA; Avandi, Raymond Ivano (Jurnal Prestasi Olahraga, 2013)
Physical fitness is an important factor in supporting the activity of people in dailyactivities.Yet many people are willing to do the activities of sport routinely, especially thosethat are older and shall tread upon an advanced age. In the county of caruban appear a clubsports hitchhike arca hash club with a majority of its members are aged above 40 years to seehow the influence of sports events hitchhike arca hash club against fitness corporeal we needto hold research level health condition for people who have followed this activity regularly.So that it can be obtained the results and material inputs in its evaluation exercise program toimprove health condition arca hash club members of district caruban and society in general.The kind of research is using the quantitative through study descriptive. This researchdescribed results of data of the health condition for people over 40 years of age who follows aroutine arca hash club district caruban. The subject of this research is a member of the club a.sarca hash over 40 years old of 36 people. Only using a method of collecting data, a test onresearchers also use methods a questionnaire untik furnish data qualitative research.Results of physical fitness test on arca hash club district caruban show differencescriteria that influenced by some factors: conditions among other participants at the time of thetest a preparatory condition before the test, participants how long participants have joined theactivity arca hash club, the activity of other sports outside kegitan arca hash club, the level ofroutine exercises, participants in following motivation at the time of the test the level ofknowledge participants against fitness and physical ability to apportion time. Can beconcluded that the activity of sports hitchhike done by arca hash club district caruban havingclimate change to increasing public health condition of age at over 40 years.